DETERMINATION OF REM IN URANIUM ORES OF THE SHU-SARYSU URANIUM-ORE PROVINCE BY INDUCTIVELY COUPLED PLASMA ATOMIC EMISSION SPECTROMETRY - А. К. Тorebekov; M. S. Kalmakhanova; B. K. Massalimova (Academic Scientific Journal of Chemistry, 2021)
This article discusses the features of the determination of elements in uranium ores of the Shusarysu uranium-ore province by inductively coupled plasma atomic emission spectrometry in comparison with the ore standard of Ore Research & Exploration (Australia). A multi-stage method of sample preparation for measurement is considered. The existing and developed methods for determining the elemental composition of uranium ores are focused, as a rule, on the determination of specific elements using regulated analysis procedures. However, during routine analysis, we need to quickly and efficiently determine a larger list of elements available with one instrumental method. Various methods are used to obtain multielement analysis, among which mass spectrometry and inductively coupled plasma atomic emission analysis are most popular due to their high performance and low detection limits. The listed methods work with solutions, therefore, it is necessary to pay great attention to sample preparation and instrument calibration. The invention relates to a method for preparing samples for the study of materials by determining their chemical properties in a liquid state, for example, using inductively coupled plasma spectrometry. The method for preparing silicate and carbonate rock samples for spectrometric analysis includes autoclave decomposition of samples in a mixture of concentrated acids in a microwave oven at temperature and pressure and cooling the samples. Then carry out the introduction of the internal standard and bringing to the standard volume